The Potential of Mediation in the Resolution of Crimes of Ecocide - Walti, Stephanie (Department of Commercial Law, 2021)
This minor dissertation deals with the question of whether there is a potential for mediation in relation to the resolution of conflicts concerning the crime of ecocide. First, the terminology and conceptuality are presented and an analysis of the situation regarding mediation in the solution of ecocide crimes is prepared. The potential of mediation for ecocide crimes is then discussed and clarified on the basis of the findings. The minor dissertation is based on the evaluation of relevant literature and the investigation of case studies (in particular mock trials). By doing so, the author aims to gain insights into how we can effectively combat ecocide and thus protect the environment – our very basis of life.